Purification and characterization of two β-glucosidases from the thermophilic fungus Thermoascus aurantiacus - De Palma-Fernandez, E. R.; Gomes, E. [UNESP]; Da-Silva, R. [UNESP] (Springer Nature, 2002)
β-Glucosidase from the fungus Thermoascus aurantiacus grown on semi-solid fermentation medium (using ground corncob as substrate) was partially purified in 5 steps-ultrafiltration, ethanol precipitation, gel filtration and 2 anion exchange chromatography runs, and characterized. After the first anion exchange chromatography, β-glucosidase activity was eluted in 3 peaks (Gl-1, Gl-2, Gl-3). Only the Gl-2 and Gl-3 fractions were adsorbed on the gel matrix. Gl-2 and Gl-3 exhibited optimum pH at 4.5 and 4.0, respectively. The temperature optimum of both glucosidases was at 75-80°C. The pH stability of Gl-2 (4.0-9.0) was higher than Gl-3 (5.5-8.5); both enzyme activities showed similar patterns of thermostability. Under conditions of denaturing gel chromatography the molar mass of Gl-2 and Gl-3 was 175 and 157 kDa, respectively. Using 4-nitrophenyl β-D-glucopyranoside as substrate, Km values of 1.17 ± 0.35 and 1.38 ± 0.86 mmol/L were determined for Gl-2 and Gl-3, respectively. Both enzymes were inhibited by Ag+ and stimulated by Ca2+.
Keywords: beta glucosidase; calcium; silver; Ascomycetes; Brazil; chemistry; drug antagonism; enzymology; gel chromatography; ion exchange chromatography; isolation and purification; kinetics; metabolism; molecular weight; pH; polyacrylamide gel electrophoresis; precipitation; ultrafiltration; Ascomycota; beta-Glucosidase; Calcium; Chromatography, Gel; Chromatography, Ion Exchange; Electrophoresis, Polyacrylamide Gel; Hydrogen-Ion Concentration; Kinetics; Molecular Weight; Precipitation; Silver; Ultrafiltration